2008
DOI: 10.4161/cc.7.2.5361
|View full text |Cite|
|
Sign up to set email alerts
|

Specific isoforms of p73 control the induction of cell death induced by the viral proteins, E1A or Apoptin

Abstract: A member of the p53 family, p73, has several isoforms and differentially regulates transcription of genes involved in the control of the cell cycle and apoptosis. We have previously shown efficient and p53-independent, tumor-specific cell death induced by the viral proteins E1A and Apoptin. Here, we demonstrate that the induction of apoptosis by these viral proteins involves activation of TAp73. Both E1A and Apoptin induced expression of endogenous TAp73 and the p53/p73 BH3-only pro-apoptotic target, PUMA, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Over the last few years, several studies have suggested specific roles for particular p73 isoforms (De Laurenzi et al 1998;Murray-Zmijewski et al 2006;Klanrit et al 2008). Thus, these data indicate that the ratio of various p73 isoforms present in an individual cell determines the outcome of p73 function, rather than the sum of the activities of each isolated p73 isoform.…”
mentioning
confidence: 81%
“…Over the last few years, several studies have suggested specific roles for particular p73 isoforms (De Laurenzi et al 1998;Murray-Zmijewski et al 2006;Klanrit et al 2008). Thus, these data indicate that the ratio of various p73 isoforms present in an individual cell determines the outcome of p73 function, rather than the sum of the activities of each isolated p73 isoform.…”
mentioning
confidence: 81%
“…Interaction of certain viral proteins with key cellular components such as p53 and pRB causes deregulation of the cell cycle program and consequently cellular transformation. Additionally, there is clear evidence for the role of viruses, through the specific function of viral proteins such as E1A of human adenovirus, in the induction of tumour specific cell death [43,50,51]. The potential use of viruses and viral derived proteins in cancer therapy is of major interest at present.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, we have recently shown that apoptin induces the expression of the p53/p73 pro-apoptotic target PUMA [43]. To further investigate the importance of PUMA in apoptin-induced apoptosis, PUMA knockout HCT116 cells were investigated.…”
Section: Puma Is Important For Apoptin-induced Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations